ANALISIS KINERJA KEUANGAN DAN PERGERAKAN SAHAM PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK. MENGGUNAKAN RASIO LIKUIDITAS DAN PASAR (2021-2023) - Aprilyani, Ajeng; Aryani, Triana Siti; Purnamasari, Linda Mauliani (J-MIND (Jurnal Manajemen Indonesia), 2024)
The aim of this research is to analyze the influence of liquidity and market price variables on the financial performance and share price movements of PT. Sido Muncul Herbal Medicine and Pharmaceutical Industry 2021-2023. The research methodology used is quantitative descriptive analysis, namely analyzing a sample of companies based on the 2021-2023 financial reports. In this research, the independent variables include Current Ratio, Quick Ratio, Cash Ratio, Price to Earnings Ratio, and Price to Book value. The research results show that high liquidity makes a positive contribution to financial performance, while stock valuation measurements influence stock price fluctuations.